Chile : a country study - Hudson, Rex A. (Area handbook series., 1994)
"Compendium of Chile's history, social conditions, economic trends, and education written by knowledgeable scholars. Indicated as a basic reading source for academics, military, and travellers. Good bibliography"--Handbook of Latin American Studies, v. 57.